Keanekaragaman Spesies Amfibi (Ordo Anura) di Kawasan Taman Wisata Alam Kerandangan Kabupaten Lombok Barat - Agustini, Putu Linda; Ilhamdi, Mohammad Liwa; Hadiprayitno, Gito (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Amphibians are vertebrate animals that generally live in humid forest areas. Amphibians can be used as environmental bioindicators because of their sensitivity to environmental changes such as water pollution and destruction of native habitats. Anura is one of the group of amphibians. The occurrence of microclimate changes caused by the dynamics of biotic and abiotic factors can result in changes in the amphibian population in Kerandangan Nature Park. Recording and identifying the presence of amphibians will help maintain limited populations and potentially be managed for the better. The purpose of this study was to analyze the diversity index of amphibian species (order anura) in Kerandangan Nature Tourism Park. The method used is VES (Visual Encounter Survey). The research was conducted in 4 blocks, namely intensive utilization blocks, limited utilization, rehabilitation and protection. Data were analyzed using the Shanon-Wienner diversity index. The results of the study found 3 species of amphibians (order anura) namely Limnonectes kadarsani, Duttaphrynus melanostictus, and Polypedates leucomystax. with an amphibian diversity index (Ordo Anura) in Kerandangan Nature Tourism Park is HêžŒ = 1.07.